Spatial variations and multilevel mixed effect analysis on determinants factors of modern contraceptive utilization among reproductive age women in Ethiopia; proven by Ethiopian mini demographic health survey 2019 - Gosa Mankelkl; Beletu Kinfe (BMC, 2023)
Abstract Introduction Globally, in 2019, there are 1.9 billion women of reproductive age (15-49), of which 1.1 billion have a need for family planning. Of these, 842 million use contraceptives, and 270 million still have an unmet need for contraception. Ethiopia is a low-income country with inadequate access to family planning (FP), especially in the developing regions. The Ethiopian government was striving to increase the number of health facility in order to provide quality maternal care and services. Increasing the modern contraceptive prevalence rate is one of the goals of the government to reduce maternal and child mortality and morbidity. Methods Secondary data analysis was conducted using data from mini-EDHS of 2019 demographic and health Survey datasets. The study comprised a total of 8885 reproductive-age women. Spatial variations and multilevel mixed effect analysis on determinants factors of modern contraceptive use among reproductive age women in Ethiopia; evidenced by mini-EDHS 2019. Finally, the percentage and odd ratio, its 95% confidence intervals, and the result of spatial analysis were reported. Result This study includes a total weighted sample of 8885 reproductive-age women from the 2019 mini-Ethiopian demographic and health survey. The prevalence of modern contraceptive use was 25.5% in Ethiopia. living in urban area [AOR = 2.13; 95% CI = (1.75, 2.61); P = 0.000], being married [AOR = 1.42; 95% CI = (1.19, 1.70); P = 0.000] were found positively associated with contraceptive use. In contrast to this, attending primary education [AOR = 0.91; 95% CI = (0.74, 1.12); P = 0.000]., being Muslim [AOR = 0.25; 95% CI = (0.22, 0.29); P = 0.000], being poorest [AOR = 0.54; 95% CI = (0.45, 0.66); P = 0.000] were found negatively associated with contraceptive use. Conclusion In this study Individual and community level factors were associated with modern contraceptive use and also there were spatial variations in modern contraceptive use across the region among reproductive-age women. Empowering women to have better educational status, improving the wealth index, promoting marriage, creating awareness among rural residences women and promoting education about modern contraceptives through religiously acceptable persons, and promoting modern contraceptive use in developing regions were the key factors to improve modern contraceptive use among reproductive age women in Ethiopia.